Hubungan Tayangan Iklan Sisipan Televisi di Sinetron dengan Minat Beli - Akhlasya Pusti Rafdinia; Oji Kurniadi (UNISBA Press, 2022)
Abstract. With the development of the current era of information and media flows continues to grow, the business world is also growing and competition is getting tighter. Advertising on television is a very important way for businesses to advertise their products. The development of the current era is also advertising shows on television in the pack with attractive so that consumers are interested in buying the product. This research was conducted to find out if there is a relationship between the ad impression of lemonilo noodle inserts in soap operas ikatan cinta and the interest of buying viewers. The theory used in this study is the Hypodermic Needle theory. The method used is quantitative, with data obtained through an online questionnaire distributed to 100 respondents who are followers of @ikatancinta_review Instagram account. The data analysis technique carried out in this study is statistical analysis of data using SPPS24 presented in the form of tables and descriptive elaboration. The results of this study showed a very strong relationship between the ad impression of lemonilo noodle inserts in the soap opera love bond with the interest of buying viewers with a correlation coefficient value of 0.653. Abstrak. Dengan berkembangnya zaman saat ini arus informasi dan media terus berkembang, dunia usaha juga semakin berkembang dan persaingan semakin ketat. Iklan di televisi merupakan jalan yang sangat penting bagi pelaku usaha untuk mengiklankan produknya. Semakin berkembangnya zaman saat ini juga tayangan iklan di televisi di kemas dengan menarik agar para konsumen tertarik untuk membeli produk tersebut. Penelitian ini dilakukan untuk mengetahui apakah terdapat hubungan antara tayangan iklan sisipan mie lemonilo pada sinetron ikatan cinta dengan minat beli penonton. Teori yang digunakan pada penelitian ini adalah teori Jarum Hipodermik. Metode yang digunakan adalah kuantitatif, dengan data yang diperoleh melalui kuesioner online yang disebar kepada 100 responden yang merupakan followers dari akun Instagram @ikatancinta_review. Teknik analisis data yang dilakukan pada penelitian ini yaitu analisis statistik data menggunakan SPSS 24 yang disajikan dalam bentuk tabel dan penjabaran deskriptif. Hasil penelitian ini menunjukan adanya hubungan yang sangat kuat antara tayangan iklan sisipan mie lemonilo pada sinetron ikatan cinta dengan minat beli penonton dengan nilai koefisien korelasi sebesar 0.653.